Vorheriges Oberkörpertraining beeinträchtigt die Leistung beim 4-km-Radzeitfahren, ohne die neuromuskuläre Funktion zu verändern - Bertuzzi, R.; Silva-Cavalcante, M. D.; Guimaraes Couto, P.; de Almeida Azevedo, R.; Boari Coelho, D.; Zagatto, A.; Lima-Silva, A. E.; Millet, G. Y. (Research Quarterly for Exercise and Sport, 2021)
Purpose: This study investigated the effects of previous exhaustive upper body exercise on performance and neuromuscular fatigue following a 4-km cycling time-trial (4-km TT). Methods: Eight recreational cyclists performed a 4-km TT with (ARMPRE) or without (CONTR) a previous arm-crank maximal incremental test. In each experimental session, neuromuscular fatigue was evaluated with a series of electrically evoked and maximal voluntary isometric contractions (MVC). Oxygen uptake (V?O2), heart rate, electromyographic muscle activity (EMGRMS) and rating of perceived exertion (RPE) were also recorded throughout the 4-km TT. Results: The average power output during the 4-km TT was reduced (P = .027) for the ARMPRE (299 ± 59 W) group, compared with CONTR (310 ± 59 W) and overall performance in 4-km TT was impaired (P = .021) in ARMPRE (382 ± 28 s) compared with CONTR (376 ± 27 s). The decrease observed in MVC (P = .033) and potentiated peak twitch force (P = .004) at post-TT were similar between the ARMPRE and CONTR conditions (P = .739 and P = .493, respectively). There was no (P = .619) change in voluntary activation at post-TT between conditions. V?O2, EMGRMS and RPE measured throughout the 4-km TT were not significantly different between the conditions (P = .558, P = .558 and P = .940, respectively). The rate of RPE change relative to power output average and heart rate was higher (P = .030 and P = .013, respectively) in ARMPRE (0.031 ± 0.018 AU/W and 168 ± 8 bpm) than CONTR (0.022 ± 0.010 AU/W and 161 ± 7 bpm). Conclusion: These results suggest that impaired performance in ARMPRE was mostly due to pronounced perception of effort rather than neuromuscular fatigue.